Analisis Perbandingan Metode Interior Gateway Protocol RIP Dengan OSPF Pada Jaringan MPLS-VPLS - Yanuar Nurdiansyah; Nail Pratama; Muhammad Ifantara Putra; Muhammad Ali Sya’roni (INFORMAL: Informatics Journal, 2020)
Routing is a process for forwarding network packets from one network such as static routing and dynamic routing. This research will evaluate and implement protocols in dynamic routing such as RIP (Routing Information Protocol) and OSPF (Open Short Path First). What will later be simulated with GNS3, from this study will be obtained results For traceroute, OSPF is about 7% faster than RIP time, while for ping, OSPF is 5.9% faster than RIP and for traceroute in the topology the average result of the average traceroute time is 2.58 for RIP and 2.23 for OSPF.